Design and analysis of polar coded cooperation with incremental redundancy for IoT in fading channels - Hao Liang; Aijun Liu; Jincheng Dai; Jie Liu; Chao Gong (IET Communications, 2021)
Abstract In this study, a coded cooperation scheme using polar codes is explored for high‐reliability and low‐user complexity applications such as Internet of Things. Firstly, the cooperation way among the users is carefully designed based on systematic polar codes and cooperative decoding, without decode‐and‐forward protocol at the cooperative user. Meanwhile repetition aided code construction and decoding algorithm of polar code is proposed for the non‐cooperative case in terms of imperfect inter‐user channel. Performance analysis and numerical simulation demonstrate the bit‐error‐rate advantages of proposed polar coded cooperation in fading channels, compared to the no‐cooperation case and normal coded cooperation schemes. Furthermore, overall rate of proposed polar‐coded cooperation is considered to optimize adaptively to increase throughput efficiency.